2005
DOI: 10.1021/jm040894o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 14-Alkoxymorphinans. 22. Influence of the 14-Alkoxy Group and the Substitution in Position 5 in 14-Alkoxymorphinan-6-ones on in Vitro and in Vivo Activities

Abstract: Novel 14-alkoxy-substituted (e.g. allyloxy, benzyloxy, naphthylmethoxy) morphinan-6-one derivatives were synthesized and biologically evaluated. Compounds 6-9 and 11 displayed affinities in the subnanomolar range to mu opioid receptors which were comparable to 14-O-methyloxymorphone (1) and 14-methoxymetopon (3), and higher than oxymorphone (2). Opioid binding affinity was sensitive to the character and length of the substituent in position 14. In smooth muscle preparations they behaved as potent agonists. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 21 publications
6
68
0
Order By: Relevance
“…In line with in vitro experimental data on the high μ-OR affinity ( K i = 0.97 nM), 23 the results of the docking study revealed that 1 binds to the μ-OR in a highly favorable manner with all of the predicted interaction patterns (Table 2). The polar group at position 3 of 1 is involved in a hydrogen-bonding network formed with a few water molecules that are present in the binding pocket and mediate interactions from the ligand to the receptor via H297 6.52 .…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In line with in vitro experimental data on the high μ-OR affinity ( K i = 0.97 nM), 23 the results of the docking study revealed that 1 binds to the μ-OR in a highly favorable manner with all of the predicted interaction patterns (Table 2). The polar group at position 3 of 1 is involved in a hydrogen-bonding network formed with a few water molecules that are present in the binding pocket and mediate interactions from the ligand to the receptor via H297 6.52 .…”
Section: Resultssupporting
confidence: 78%
“…Chemical work targeted 14-arylalkyloxy-substituted derivatives of 2b , resulting in 14-benzyloxymetopon (14-BM, 4b ) 23 and the 14-phenylpropoxy-substituted analogue (PPOM, 5 ) 32 (Table 1). These derivatives bind with very high affinity to the μ-OR, comparable to that of 2b .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its ability to induce constipation, however, its potency was equal to that of morphine. 39 Several morphinan compounds reported by Grundt and coworkers have displayed mixed / ␦ agonist profi le of activity. For example, among a series of 3-hydroxy-4-methoxyindolomorphinans, compound 9 was found to display full or nearly full agonist activity at all 3 receptors in the [ 35 S]GTP ␥ S binding assay using Chinese hamster ovary (CHO) cells expressing the individual human opioid receptors.…”
Section: E120mentioning
confidence: 99%
“…Our work in the 6-ketomorphinan class of opioid analgesics has led to the design of 14-alkoxy substituted morphinan-6-ones as MOP agonists that are highly effective antinociceptive agents in various experimental models of pain [10,11]. Replacement of the hydroxyl group in position 14 of oxymorphone with a methoxy group led to 14- O -methyloxymorphone (Figure 1), which shows 9 times increased binding affinity at the MOP receptor [13] and is up to 40 times more potent in inducing an antinociceptive effect than oxymorphone in animals [14]. Furthermore, position 6 of N -methylmorphinans has been extensively targeted, and found to play a key role in ligand interaction with the MOP receptor, and also analgesic properties.…”
Section: Introductionmentioning
confidence: 99%